The Buddha's path to awakening - Shaw, Sarah (Murty Classical Library of India, 2025)
"The Buddha's Path to Awakening is the first complete prose narrative that describes Gotama Buddha's search for freedom. It starts many eons in the past when the hero of this work, Gotama Buddha, first takes the Bodhisatta vow to postpone his own awakening until the time he can teach others too. He renews this vow in the presence of Buddhas throughout history. Finally, after a long quest, he achieves his aim and becomes a Buddha. The work closes when he is fully awakened, now a teacher of gods and humans"--